Design and Implementation Of Blended Learning Approach For Simulation Education Among Undergraduate Nursing Students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of undergraduate nursing education has never been higher due to the aging population and complexity of patients. The blended simulation combined two and more educational methods and is an effective strategy in nursing education. This study was to evaluate the effectiveness of blended simulation using standardized patients and patients simulation. Using a convenience sampling, a quasi-experimental study was conducted.  Forty undergraduate nursing students enrolled and were allocated into the experimental group (n=20) or the control group (n=20). CPX (clinical performance examination) was used to evaluate physical assessment skills. Self-reporting questionnaires were used for communication skill and learning satisfaction. χ2-test/Fisher’s exact test and Mann-Whitney U test were conducted for statistical analysis. After completing the educational program, there were statistically significant higher levels of physical assessment and communication skills in the blended simulation group (p